Avaliação do promotor OCT-4 de equinos em uma abordagem transgênica em células-tronco embrionárias de murinos - Gonçalves, Fernanda da Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
O fator de transcrição Oct-4 é bem conservado entre as espécies e é conhecido por ser expresso em embriões e células-tronco embrionárias (CTE), sendo um importante marcador da pluripotência. Recentemente, foi relatado que a combinação de Oct-4 com três outros fatores de transcrição Klf-4, c-Myc e Sox2 foram capazes de reprogramar células somáticas a um estado indiferenciado pluripotente, chamadas células-tronco pluripotentes induzidas (“células iPS”), as quais apresentam várias das mesmas propriedades das CTE incluindo a pluripotência, auto-renovação e proliferação. O objetivo desse estudo foi avaliar a funcionalidade do promotor Oct-4 de eqüino em CTE de murinos. Três vetores plasmidiais expressando GFP (“green fluorescent protein”) sob o controle do promotor Oct-4 de equinos, camundongo e quatro vetores lentivirais, também contendo o gene reporter GFP e os promotores Oct-4 de equinos, camundongo e humanos, pLZ2-ecOCT-EGFP (meq) (sequência equivalente de camundongos), pLZ2-ecOCT-EGFP (heq) (sequência equivalente de humanos), pLZ2-mOCT-EGFP e pLZ2-hOCT-EGFP, respectivamente, foram construídos. Todos os vetores também contêm um sítio de resistência à blasticidina que permite a seleção das células estáveis e das células transduzidas. Essas construções plasmidiais foram verificadas se funcionavam eficientemente, bem como o efeito do promotor Oct-4 em transfectar transientes e estáveis CTE. As construções com promotor Oct-4 de camundongo, humano e eqüino (sequência análoga à de camundongo) produziram somente 6% de células GFP positivas com intensidade de fluorescência (IF) >1000 pela análise em citômetro de fluxo, enquanto que o plasmídeo contendo o promotor Oct-4 de eqüino (sequência equivalente à de humanos) produziu menos células GFP positivas (>3%) com IF >1000, quando...

The pluripotency transcription factor Oct-4 is well conserved among species and is known to be expressed in embryos and embryonic stem (ES) cells; it is being an important pluripotency marker. It was recently demonstrated that the combination of Oct-4 with three other factors Klf-4, c-myc and Sox2 were able to reprogram somatic cells to a pluripotent and undifferentiated state. These cells known as induced pluripotent stem (iPS) cells share several properties with ES cells including self-renewal, proliferation and pluripotency. The aim of this study was to assess the functionality of the horse Oct-4 promoter in mouse ES cells. Three plasmids vectors expressing GFP (green fluorescent protein) under the control of the horse, mouse and four lentivirus vectors also containing reporter gene GFP and horse, mouse and human promoters, pLZ2-ecOCT-EGFP (mouse sequence equivalent), pLZ2-ecOCT-EGFP (human sequence equivalent), pLZ2-mOCT-EGFP and pLZ2-hOCT-EGFP, respectively, were built. All these vectors also contain a blasticidin resistance cassette to allow selection of transfected stable cells and transduced cells. Afterwards, to assess the functionality of the Oct-4 promoter all plasmids were tranfected the into transient and stable mouse ES cells. Constructs with mouse, human and horse (mouse analog sequence) Oct-4 promoter produced only 6% GFP positive cells with fluorescence intensity (FI)>1000 by 20 FACs assay, while plasmid horse (human analog sequence) Oct-4 promoter produced less GFP positive cells (>3%) with FI>1000, when compared with the positive control and among groups. However, GFP expression was not present in stable cells, whereas there were Blasticidin-resistant colonies-forming from 6 days post-transfection. To optimize the system in mouse ES cells, pLZ2-mOCT-EGFP and pLZ2-hOCT-EGFP lentivectors, were tested as controls. It was used HIV-1-derived... (Complete abstract click electronic access below)
Keywords: Reprodução animal; Promotor Oct-4; Lentivetor; Vetor plasmidial; Células tronco embrionárias; Transfecção; Transdução; Oct-4 promoter; Lentivirus vector; Plasmids vector; Embryonic stem cell; Transfection; Transduction